Analisis Rasio Keuangan Perbankan Terhadap Profitabilitas - Yunanto, Yogi; Suhariadi, Fendy; Yulianti, Praptini (E-Jurnal Akuntansi; Vol 29 No 2 (2019), 2019)
This study was conducted to examine the effect of variable bank size, LDR, NPL, BOPO, NIM, on ROA in the regional development banking industry in Indonesia. The method in data collection, an explanation of the definition of operational variables, and a technical explanation of the analysis will be carried out using quantitative methods. The results of this study support the Bank Loan Rate Mark Up Theory where LDR, NPL and NIM affect ROA, with increasing interest gains can increase ROA. Keywords : Financial Ratios; Profitability.